Communication performance analysis of wireless sensor network for railway environmental monitoring - Ruifeng CHEN; Ming NI; Chunjie XU; Hao HU (Dianxin kexue)
Wireless sensor network (WSN) deployed along the railway can be commonly applied to environmental monitoring.In order to lengthen the lifetime of WSN,it is essential to introduce the node sleeping mechanism.Therefore,firstly the stochastic process theory was adopted and an analytical framework was proposed to study the communication performance of WSN in railway scenarios based on the node sleeping mechanism.Furthermore,the impacts of different system factors on the reception performance of WSN were analyzed under railway scenarios,and then the relation between the optimal ratio of active nodes and other system factors could be obtained.A simulation platform was established to verify the reception performance of WSN in safety areas and hazards-prone sections respectively.Finally,practical case was presented to verify the deployment scheme based on node sleeping mechanism.The analytical results could provide the guidelines for practical deployment of WSN under railway scenarios.